Collaborative Risk and Change Governance in BPM Projects: The MAP-BPM Approach - Correa Junior, Giovanni Evaristo; Vilela, Jéssyka (Anais Estendidos do Simpósio Brasileiro de Sistemas Colaborativos (SBSC); 2026: Anais Estendidos do XXI Simpósio Brasileiro de Sistemas Colaborativos, 2026)
Context: BPM projects involve socio-technical changes that require communication, coordination, and shared decision-making among multiple stakeholders; however, risk analysis and change management are often treated separately, limiting collaborative governance. Objective: This paper proposes MAP-BPM, a methodology that integrates risk analysis and change management across the BPM lifecycle to support collaborative assessment and multi-stakeholder coordination. Method: The approach was grounded in a Systematic Literature Review and evaluated through surveys with BPM professionals. Results: Integrating risk and change improves transparency, decision traceability, stakeholder alignment, and organizational resilience. Conclusions: The study advances collaborative governance in BPM by providing a structured methodology for integrated socio-technical process transformation.